. Issue 2 (March 2015) - Beckers, Oliver M.; Anderson, Wendy; Moczek, Armin P.
SUMMARY: The dung beetle, Onthophagus taurus, was introduced <50 years ago from its native Mediterranean range into Western Australia (WA) and the Eastern United States (EUS). The intensity of intra‐ and interspecific competition for dung as a breeding resource is substantially higher in WA. First, we tested whether differential resource competition in the two exotic ranges is associated with divergences in life history traits, which impact on resource use. We predicted that high levels of resource competition in WA should favor females that produce brood balls more efficiently and of altered size, and produce offspring more readily when a breeding opportunity arises. Furthermore, we predicted that larvae from WA populations may have evolved more efficient development and thus exhibit higher eclosion success, shorter development time, and altered body size under standardized conditions. Second, we examined the likely developmental mechanisms underlying these divergences, that is, genetic differentiation, developmental plasticity, or parental effects in a common garden experiment. Field‐collected EUS and WA populations significantly differed, as predicted, in most of the traits examined. However, these differences are facilitated by a complex combination of proximate mechanisms. Developmental plasticity and (grand) parental effects mediated differences related to reproductive performance, whereas genetic differentiation mediated differences in the duration of larval development. Our study highlights that population divergences can be the product of a patchwork of proximate mechanisms, with each mechanism adjusting different traits in a way that the resulting composite phenotype may be better suited to its competitive environment.